Sericin-mediated improvement of dysmorphic cardiac mitochondria from hypercholesterolaemia is associated with maintaining mitochondrial dynamics, energy production, and mitochondrial structure - Kitiya Rujimongkon; Sumate Ampawong; Duangnate Isarangkul; Onrapak Reamtong; Pornanong Aramwit (Taylor & Francis Group, 2022)
Context Sericin is a component protein in the silkworm cocoon [Bombyx mori Linnaeus (Bombycidae)] that improves dysmorphic cardiac mitochondria under hypercholesterolemic conditions. This is the first study to explore cardiac mitochondrial proteins associated with sericin treatment.Objective To investigate the mechanism of action of sericin in cardiac mitochondria under hypercholesterolaemia.Materials and methods Hypercholesterolaemia was induced in Wistar rats by feeding them 6% cholesterol-containing chow for 6 weeks. The hypercholesterolemic rats were separated into 2 groups (n = 6 for each): the sericin-treated (1,000 mg/kg daily) and nontreated groups. The treatment conditions were maintained for 4 weeks prior to cardiac mitochondria isolation. The mitochondrial structure was evaluated by immunolabeling electron microscopy, and differential mitochondrial protein expression was determined and quantitated by two-dimensional gel electrophoresis coupled with mass spectrometry.Results A 32.22 ± 2.9% increase in the percent striated area of cardiac muscle was observed in sericin-treated hypercholesterolemic rats compared to the nontreatment group (4.18 ± 1.11%). Alterations in mitochondrial proteins, including upregulation of optic atrophy 1 (OPA1) and reduction of NADH-ubiquinone oxidoreductase 75 kDa subunit (NDUFS1) expression, are correlated with a reduction in mitochondrial apoptosis under sericin treatment. Differential proteomic observation also revealed that sericin may improve mitochondrial energy production by upregulating acetyl-CoA acetyltransferase (ACAT1) and NADH dehydrogenase 1α subcomplex subunit 10 (NDUFA10) expression.Discussion and conclusions Sericin treatment could improve the dysmorphic mitochondrial structure, metabolism, and energy production of cardiac mitochondria under hypercholesterolaemia. These results suggest that sericin may be an alternative treatment molecule that is related to cardiac mitochondrial abnormalities.